Early enteral vs. oral nutrition after Whipple procedure: Study protocol for a multicentric randomized controlled trial (NUTRIWHI trial) - Joliat, Gaëtan-Romain; Martin, David; Labgaa, Ismail; Melloul, Emmanuel; Uldry, Emilie; Halkic, Nermin; Fotsing, Ginette; Cristaudi, Alessandra; Majno-Hurst, Pietro; Vrochides, Dionisios; Demartines, Nicolas; Schäfer, Markus (Frontiers in Oncology, 2022)
Background Malnutrition has been shown to be a risk factor for postoperative complications after pancreatoduodenectomy (PD). In addition, patients needing a PD, such as patients with pancreatic cancer or chronic pancreatitis, often are malnourished. The best route of postoperative nutrition after PD remains unknown. The aim of this randomized controlled trial is to evaluate if early postoperative enteral nutrition can decrease complications after PD compared to oral nutrition. Methods This multicenter, open-label, randomized controlled trial will include 128 patients undergoing PD with a nutritional risk screening ≥3. Patients will be randomized 1:1 using variable block randomization stratified by center to receive either early enteral nutrition (intervention group) or oral nutrition (control group) after PD. Patients in the intervention group will receive enteral nutrition since the first night of the operation (250 ml/12 h), and enteral nutrition will be increased daily if tolerated until 1000 ml/12 h. The primary outcome will be the Comprehensive Complication Index (CCI) at 90 days after PD. Discussion This study with its multicentric and randomized design will permit to establish if early postoperative enteral nutrition after PD improves postoperative outcomes compared to oral nutrition in malnourished patients.